ANALISIS PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KREATIF IPA KELAS VI UPT SD NEGERI 34 LIBURENG KABUPATEN PANGKEP - Muis, Abdul; Aisyiah, Sitti; Istiqama; Taswira, Ainun; Arief, Tarman A (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creative thinking is one of the essential 21st-century skills that needs to be developed in science learning at the elementary school level. However, the results of the preliminary observation conducted at UPT SD Negeri 34 Libureng, Pangkep Regency, indicated that the learning process was still dominated by conventional teaching methods, the use of instructional media had not been optimized, and students' creative thinking skills were relatively low. This study aimed to analyze the implementation of the Project Based Learning (PjBL) model assisted by instructional videos in improving the creative thinking skills of sixth-grade students in science learning. In addition, this study described the implementation of learning based on the stages of planning, implementation, and evaluation, as well as students' creative thinking skills in terms of fluency, flexibility, originality, and elaboration. This study employed a qualitative approach with a descriptive research design. The research was conducted at UPT SD Negeri 34 Libureng, Pangkep Regency, from May to June 2026. The research participants consisted of 15 sixth-grade students, the classroom teacher, and the school principal. Data were collected through observations, interviews, and documentation, and were analyzed using the Miles, Huberman, and Saldana interactive analysis model, which includes data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings revealed that the implementation of the Project Based Learning (PjBL) model assisted by instructional videos was carried out effectively in accordance with the PjBL syntax, covering the planning, implementation, and evaluation stages. The implementation of the model improved students' creative thinking skills in terms of fluency, flexibility, originality, and elaboration. Furthermore, students' learning participation, collaborative skills, problem-solving abilities, and learning motivation also showed noticeable improvement. The main challenges encountered were unstable internet connectivity and the need for additional guidance for some students during the initial stage of project implementation. Nevertheless, these challenges were successfully addressed by the teacher, allowing the learning process to continue effectively. Therefore, the implementation of the Project Based Learning (PjBL) model assisted by instructional videos made a positive contribution to the development of students' creative thinking skills in elementary science learning.